Amperometric Sensing of H2O2 using Pt-TiO2/Reduced Graphene Oxide Nanocomposites - Leonardi, Salvatore Gianluca
Nanostructures made of titanium dioxide and/or platinum nanoparticles supported on reduced graphene oxide (RGO) were synthesized by a simple and fast microwave-assisted route and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier-transform infrared (FTIR) and Raman spectroscopies. The composites consist of RGO sheets fully and homogeneously coated with a dense layer of 8 nm TiO2 and/or 2 nm Pt nanoparticles. Screen-printed flexible sensors based on Pt-TiO2/RGO composites are applied for the amperometric detection of hydrogen peroxide ( H2O2). The electrochemical characteristics of Pt/RGO, TiO2/RGO and Pt-TiO2/RGO-modified screen printed electrodes are investigated and discussed. The developed sensor allows the detection of H2O2, with a linear response from 0 to 20 mm of H2O2 and a sensitivity of 40 mu AmM-1 cm(-2). The resulting device is also suitable for the analysis of this toxic compound in milk.